Socialization of the Importance of Physical Activity to Improve Health in Postpartum Mothers at Garut Hospital - Sukmawati; Furkon Nurhakim; Lilis Mamuroh (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
Failure of involution after childbirth can be caused by postpartum mothers not doing physical activity, resulting in thrombophlebitis, infection, and continued bleeding. Physical activity can be done with early mobilization and postpartum exercises to improve blood circulation and prevent blood flow from being obstructed. The purpose of this community service is to hope that postpartum mothers have good knowledge about the importance of activities in preventing complications after giving birth. This method of community service is health education about the importance of physical activity in postpartum mothers, with a target of 10 postpartum mothers who are treated at Garut Hospital. The media used are leaflets and PowerPoints. To assess the effectiveness of health education before giving material, a pre-test is carried out, and after giving material, a post-test is given. The results of the service showed an increase in knowledge among postpartum mothers about physical activity. It is expected that the physical activity of postpartum mothers can be carried out continuously while at home and after returning home.